Beyond reciprocal: the role of platforms in diffusing data value across multiple stakeholders. (16th October 2019) - Malthouse, Edward C.; Buoye, Alexander; Line, Nathaniel; El-Manstrly, Dahlia; Dogru, Tarik; Kandampully, Jay
Abstract : Purpose: The purpose of this paper is to assess the role of platforms in diffusing data value across multiple stakeholders. Design/methodology/approach: Seminal theoretical and managerial work has been critically examined in order to justify the need for improving/extending the contemporary understanding of the data value creation process. Findings: The results suggest that existing frameworks and conceptualizations of reciprocal data value provide incomplete understanding of the role of platforms in data value diffusion. Research limitations/implications: This paper provides service researchers with a better understanding of the role of platforms in data value diffusion. Future research can develop and validate new frameworks that reflect the proposed extended/improved view of data value creation. Practical implications: Service and hospitality managers will be able to more effectively manage the role of platforms in data value diffusion. Specifically, this paper proposes that, in order for data to become a source of competitive advantage, there must be a symbiotic relationship among all the stakeholders of the data ecosystem. Originality/value: The authors discuss how data creates value for different stakeholders in the hospitality industry.